Identifikasi Boraks dalam Bakso di Kelurahan Bahagia Bekasi Utara Jawa Barat dengan Metode Analisa Kualitatif - Mega Efrilia; Tria Prayoga; Nur Mekasari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
Already a research identification of boraks in meatball a sell is Kelurahan Bahagia, Nort Bekasi East Java. A research as a purpose for identification boraks in meatball with a metode analysis kualitatif that is a burn of fire a testing colour with a turmeric paper with ake use AgNO3, and BaCl2. Sampel in take by metode random sampel plainin meatball a sell a is Kelurahan Bahagia Nort Bekasi. On a test result, the testing in apprearance meatball of in point negatif contain boraks because meatball not a springy, bases in one day, colour not white, and slimy in one day. in akualitatif this testing 15 sample meatball with test burn of fire, by test colour a using turmeric paper, and BaCl2 negatif contain a boraks.